The Role of Self-Efficacy as a Mediator in Relationships Education Support with Entrepreneurial Intention - Herdiyan Radityo; Sahrani Ong Putri; Meisya Puti Khairunnisa; Anna Suzana (Publikasi Indonesia, 2024)
Extreme poverty is a major problem plaguing the Indonesian economy. As a result of labor parity and employment, entrepreneurship can slow the pace of decline by creating additional job opportunities. The purpose of this study was to determine the role of self-efficacy as a moderator between entrepreneurship education and aspirational entrepreneurship. Quantitative methods are used in associative research. Questionnaires are used for data collection purposes. Of the 530 students who participated in the study, 90 were used as samples. Structural Equation Modeling (SEM) data analysis was performed using SmartPLS 3.0 devices. The findings of this study suggest that educational entrepreneurship greatly increases aspirations to start one's own business. Research shows that educational entrepreneurship increases students' confidence. affects the correlation between entrepreneurship education and aspirations to start one's own venture in a highly profitable way.